Light clusters in nuclear matter: excluded volume versus quantum many-body approaches - Hempel, Matthias; Schaffner-Bielich, Jürgen; Typel, Stefan; Röpke, Gerd (Physical review. C, Nuclear physics, 2011)
The formation of clusters in nuclear matter is investigated, which occurs, e.g., in low-energy heavy-ion collisions or core-collapse supernovae. In astrophysical applications, the excluded volume concept is commonly used for the description of light clusters. Here we compare a phenomenological excluded volume approach to two quantum many-body models, the quantum statistical model and the generalized relativistic mean-field model. All three models contain bound states of nuclei with mass number A≤4. It is explored to which extent the complex medium effects can be mimicked by the simpler excluded volume model, regarding the chemical composition and thermodynamic variables. Furthermore, the role of heavy nuclei and excited states is investigated by use of the excluded volume model. At temperatures of a few MeV the excluded volume model gives a poor description of the medium effects on the light clusters, but there the composition is actually dominated by heavy nuclei. At larger temperatures there is a rather good agreement, whereas some smaller differences and model dependencies remain.
Gesehen am 12.10.2022